ANALYSIS OF FAMILY ECONOMIC RESILIENCE OF LAYER CHICKEN EGG FARMERS IN SUSUT DISTRICT, BANGLI REGENCY - Luh Putu Trisna Resty Amara; Amrita Nugraheni Saraswaty (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Family economic resilience refers to the household’s ability to meet basic needs, manage assets, and protect itself from economic risks. Susut District, Bangli Regency, was chosen as the research site because it represents one of the major centers of egg production in Bali. This study aims to analyze the effects of location, income, savings, education of the household head, home ownership, and health insurance on the economic resilience of farming families. The research population consisted of 95 farming households, all of which were used as the sample through purposive sampling. Data were analyzed using binary logistic regression, with family economic resilience defined as the fulfillment of at least three out of five resilience criteria. The results indicate that simultaneously, all variables significantly affect family economic resilience. Partially, income, education of the household head, home ownership, and health insurance exert significant effects, while location and savings do not.